Higher Tablet Use Is Associated With Better Sustained Attention Performance but Poorer Sleep Quality in School-Aged Children - Chiu, Karen; Lewis, Frances C.; Ashton, Reeva; Cornish, Kim M.; Johnson, Katherine A. (Frontiers in Psychology, 2022)
There are growing concerns that increased screen device usage may have a detrimental impact on classroom behaviour and attentional focus. The consequences of screen use on child cognitive functioning have been relatively under-studied, and results remain largely inconsistent. Screen usage may displace the time usually spent asleep. The aim of this study was to examine associations between screen use, behavioural inattention and sustained attention control, and the potential modifying role of sleep. The relations between screen use, behavioural inattention, sustained attention, and sleep were investigated in 162 6 to 8 -year-old children, using parent-reported daily screen use, the SWAN ADHD Behaviour Rating Scale, the Sustained Attention to Response Task, and the Children’s Sleep Habits Questionnaire. Tablet use was associated with better sustained attention performance but was not associated with classroom behavioural inattention. Shorter sleep duration was associated with poorer behavioural inattention and sustained attention. Sleep quality and duration did not act as mediators between screen usage and behavioural inattention nor sustained attention control. These findings suggest that careful management of the amount of time spent on electronic screen devices could have a beneficial cognitive impact on young children. The results also highlight the critical role of sleep in enhancing both behavioural attention and sustained attention, which are essential for supporting cognitive development and learning.